2021
DOI: 10.1186/s13054-021-03810-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic diferences between COVID-19 and H1N1 influenza induced ARDS

Abstract: Background Acute respiratory distress syndrome (ARDS) is a type of respiratory failure characterized by lung inflammation and pulmonary edema. Coronavirus disease 2019 (COVID-19) is associated with ARDS in the more severe cases. This study aimed to compare the specificity of the metabolic alterations induced by COVID-19 or Influenza A pneumonia (IAP) in ARDS. Methods Eighteen patients with ARDS due to COVID-19 and twenty patients with ARDS due to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
1
15
2
Order By: Relevance
“…Nevertheless, strong overall correlations between lipids and immune markers suggest a true disease-related context rather than an ICU bias. To isolate these effects, it is advised to recruit a control group of ICU patients who do not have COVID-19, (e.g., ARDS due to other pulmonary infections [ 75 ]). The lack of an appropriate control group is a limitation of our study, in addition to an imbalanced cohort across the disease stages and along the hospitalisation period.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, strong overall correlations between lipids and immune markers suggest a true disease-related context rather than an ICU bias. To isolate these effects, it is advised to recruit a control group of ICU patients who do not have COVID-19, (e.g., ARDS due to other pulmonary infections [ 75 ]). The lack of an appropriate control group is a limitation of our study, in addition to an imbalanced cohort across the disease stages and along the hospitalisation period.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a pandemic caused by coronavirus SARS-CoV-2 with mild to severe respiratory symptoms [ 48 ]. Coronaviruses and influenza are among the pandemic viruses that can cause lethal lung injuries and death from acute respiratory distress syndrome (ARDS) [ 11 , 49 ]. As was given by Earar et al [ 11 ], three clinical stages of SARS-CoV-2 infection have been described: asymptomatic stage I and II with mild and moderate symptoms, accompanied by the presence of the virus, and stage III with severe respiratory symptoms, including pneumonia, sepsis or multiple organ failure.…”
Section: Supportive Supplementation—does High-dose Vitamin C As a Die...mentioning
confidence: 99%
“…Extensive research has suggested that hyperinflammation induced by IAV is heavily involved with oxidative stress. Therefore, the elevated oxidative stress is commonly observed in IAV infected cases with severe disease progress (121)(122)(123). Consistently, several factors that are known to be associated with increased ROS levels and oxidative stress, such as chronic diseases, morbid obesity, smoking, and older age, are listed as risk factors for a more severe course on IAV infected patients (124-126).…”
Section: Discussionmentioning
confidence: 99%